Carboxylic acid recognition of diamidine having a fluorescent 1, 8-diphenylanthracene unit and its detection of amidinium-carboxylate and amidinium formation. Issue 9 (1st March 2019) - Kusukawa, Takahiro; Aramoto, Hiroki; Umeda, Takehiro; Kojima, Yusuke
Abstract: A diphenylanthracene-based diamidine (1a ) fluorescent probe for the detection of dicarboxylic acids has been designed and synthesized, which has an extended π -conjugation rather than a simple anthracene ring, in order to observe highly different fluorescence wavelengths after complex formation with dicarboxylic acids. The fluorescence spectra of the mixed solution of the diamidine1a and carboxylic acids showed two different fluorescence bands, which corresponded to the complex formation (amidinium-carboxylate formation, λ em  = 450 nm, light blue color) and dissociated amidinium formation ( λ em  = 510 nm as a broad band, green color). The complexed and dissociated states were confirmed by DOSY NMR and TD-DFT calculations. These different fluorescence wavelengths may come from the differences in the dihedral angles between the phenyl rings at the 1, 8-position and anthracene ring (difference in π -conjugation) of1a under complex formation and dissociated amidinium formation. The proposed mechanism for the observation of the different fluorescence wavelengths (complex formation and amidinium formation) was also confirmed by the fluorescence study of diamidine1b which causes restricted rotation of the phenyl rings by substitution of the steric methyl groups, and observed the same fluorescence spectra for the complex formation and amidinium formation (400, 420, 450 nm as a vibrational structure of anthracene ring). These fluorescence characteristics of the diamidine1a are also applicable for the detection of α, ω −dicarboxylic acids. Graphical abstract: Image 1